SANKSI EKONOMI AMERIKA SERIKAT TERHADAP IRAN PERIODE 2018–2020 DALAM PERSPEKTIF NEOREALISME - Fitriyanti, Rahmi; Alir, Adre (Emerald: Journal of Economics and Social Sciences, 2024)
Good relations between the United States (US) and Iran turned complex due to the important events of the 28 Mordad Coup in 1952, the 1979 Iranian Revolution, as well as disputes between the two countries regarding the issue of Iran's nuclear program. This research also explains the impact of US economic sanctions on Iran's economic conditions. However, Iran's response to these sanctions has shown to be ineffective in stopping Iran's nuclear uranium enrichment activities. The Neorealism Perspective is used as a reference in analyzing US economic sanctions against Iran for the 2018–2020 period. Meanwhile, the approach is using a qualitative research method which analysis is focused on gaining a deeper understanding of US economic sanctions against Iran based on the Neorealism Perspective. The findings obtained based on Neorealism show that the emergence of distrust between Iran and the US is due to the absence of authority in the international system. Neorealism views US economic sanctions against Iran during the 2018–2020 period as part of international political dynamics that arise from power competition in an anarchic international system. According to the Neorealism Perspective, large countries such as the US tend to use economic sanctions as a tool to influence other countries and defend their national security interests.